Factors influencing medical students’ decisions to remain at their alma mater for postgraduate clinical training: A cross-sectional study in Japan - Keiko Hamatsu; Miwa Sekine; Koshi Kataoka; Yasuhiko Kiyama; David Aune; Yuji Nishizaki (PLoS ONE, 2025)
Background Despite structured postgraduate clinical training programs in Japan, a considerable number of medical graduates have recently preferred community hospitals to university hospitals for postgraduate clinical training. Understanding the factors influencing this preference is crucial for university hospitals to attract and retain top medical talent. Objective To investigate how faculty and hospital characteristics influence medical graduates’ decisions to apply to their alma mater for postgraduate clinical training in Japan. Methods This cross-sectional study was conducted in 80 university-affiliated hospitals in Japan. Data were collected from publicly available sources, including hospital websites, the Japanese Residency Matching Program, and national databases. The variables included the proportion of medical students applying to their alma mater for postgraduate clinical training, hospital characteristics, and professors’ publication records in the top five medical journals. Univariate and multiple regression analyses were performed to assess factors associated with the proportion of medical students applying to their alma mater hospitals. Results The average proportion of medical students applying to their alma mater for postgraduate clinical training was 62.9%. The multiple regression analysis revealed that a higher proportion of alumni professors was significantly associated with a decreased proportion of graduates choosing their alma mater for postgraduate clinical training (p = .001). University hospitals located in urban areas were less likely to retain graduates than those in rural areas (p = .005). Conclusions Compared with community hospitals, university hospitals with greater heterogeneity in faculty members’ institutional origins and those located in rural areas were more successful in retaining their graduates for postgraduate clinical training. Thus, recruiting faculty from a broader range of institutions and aligning training programs with modern medical graduate preferences may enhance university hospitals’ attractiveness. Addressing these factors is essential for university hospitals in Japan to secure a well-trained physician workforce and improve healthcare outcomes.